2018
DOI: 10.1161/jaha.117.008000
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase‐4 Inhibition Potentiates Stimulated Growth Hormone Secretion and Vasodilation in Women

Abstract: BackgroundDiminished growth hormone (GH) is associated with impaired endothelial function and fibrinolysis. GH‐releasing hormone is the primary stimulus for GH secretion and a substrate of dipeptidyl peptidase‐4. We tested the hypothesis that dipeptidyl peptidase‐4 inhibition with sitagliptin increases stimulated GH secretion, vasodilation, and tissue plasminogen activator (tPA) activity.Methods and ResultsHealthy adults participated in a 2‐part double‐blind, randomized, placebo‐controlled, crossover study. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
2
Order By: Relevance
“…Triglyceride and PAI-1 levels in the women in the current study were one-third of the levels in their study population, thus making it difficult to detect further down-regulation of PAI-1 production. We have previously demonstrated that GH affects tPA activity levels through the GH receptor and downstream IGF-1 secretion,(11) but we did not observe any change in IGF-1 or tPA activity in this study. We also did not see any effect of sitagliptin on inflammation, whereas Makdissi A et al observed an anti-inflammatory effect of 100 mg daily sitagliptin on CRP, IL-6 and free fatty acids after 12 weeks in patients with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Triglyceride and PAI-1 levels in the women in the current study were one-third of the levels in their study population, thus making it difficult to detect further down-regulation of PAI-1 production. We have previously demonstrated that GH affects tPA activity levels through the GH receptor and downstream IGF-1 secretion,(11) but we did not observe any change in IGF-1 or tPA activity in this study. We also did not see any effect of sitagliptin on inflammation, whereas Makdissi A et al observed an anti-inflammatory effect of 100 mg daily sitagliptin on CRP, IL-6 and free fatty acids after 12 weeks in patients with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 90%
“…(2) We previously reported that sitagliptin increases forearm vasodilation, measured by strain gauge plethysmography, in healthy women as assessed during stimulated GH secretion with peak levels averaging 11.6 mg/dL. (11) In the present study, we did not observe any effect of sitagliptin on conduit artery vascular function, however. Mean overnight GH levels in this study in patients with PCOS were significantly lower than in our prior study in healthy women.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, at present there are no specific recommendations regarding antidiabetic medications in AGHD. Interestingly, the dipeptidyl peptidase-4 inhibitor sitagliptin has been recently demonstrated to enhance endogenous GH and IGF-1 secretion in women [ 134 ] which may be beneficial in patients with coexisting diabetes and AGHD and is worth being examined in future research.…”
Section: Insulin Resistance and Diabetes In Treated And Untreated Pat...mentioning
confidence: 99%
“…In healthy volunteers, antihypertensive effects of sitagliptin has been shown and discussed that this effect is not directly related to GLP-1 or brain natriuretic peptide concentration [106], it could induce vasodilation by increase in growth hormone secretion [107].…”
Section: Clinical Studiesmentioning
confidence: 99%